Shifting sands on Mars: insights from tropical intra‐crater dunes. Issue 4 (16th October 2012) - Geissler, Paul E.; Stantzos, Nicholas W.; Bridges, Nathan T.; Bourke, Mary C.; Silvestro, Simone; Fenton, Lori K.
ABSTRACT Evidence for sand motion is found in repeated observations of sand dunes at three sites in the Martian tropics by the High Resolution Imaging Science Experiment on Mars Reconnaissance Orbiter. An eroding outcrop of layered sediments is identified as a possible source of the sand in Pasteur crater. Ancient layered sediments in Becquerel crater are actively being carved into flutes and yardangs by the blowing sands. Dunes in an un‐named crater in Meridiani near the Mars Exploration Rover Opportunity landing site advanced as much as 50 cm over an interval of one Martian year. Copyright © 2012 John Wiley & Sons, Ltd.